Role of Behavioral Biases in Investment Decisions : A Factor Analysis - Dangi, Meghna; Kohli, Bindya (Indian Journal of Finance, 2018)
Purpose : Behavioral finance is a paradigm shift that combines psychological aspects of human behaviour with traditional finance concepts to understand investment decision making process of investors. In the course of such analysis, it brings to light some departures from rational decision making by investors which are termed as biases. In cognitively complex situations, individuals use biases to take the most optimum, but not the most rational decisions. The purpose of creating archetypes of investors is to customize investment advice based on biases exhibited by the individual investor. The benefit of archetypes is that they help in communicating a lot of information without much explanation or analysis. Hence, this is a very practical tool to assist financial service providers to understand the investment decision making process and develop more effective financial products that would help investors in achieving their investment goals. Design/Methodology : The research was primarily descriptive in nature and quantitative in approach. Survey technique through the use of a questionnaire was used to collect numerical data, which was empirically investigated via statistical computation techniques. An initial inventory of 24 items pertaining to 21 biases was assessed for validity, was subjected to pilot tests, and subsequently to various rounds of modification. The final data were collected from 389 respondents using a questionnaire that captured the biases. The archetypes were created using principal component analysis. Findings : The research came up with archetypes of investors based on heuristics and biases they exhibited. The archetypes were thus named by us as : The Stereotypical Investor, The Nervous Investor, The Imitator, The NaÃ¯ve Investor, The Cautious Investor, and The Passive Investor. Practical Implications : The paper provided a very practical tool not only to investors to understand their own biases, but also to portfolio managers about how investors differ behaviourally. This will give investors a better chance to achieve desired outcomes in the stock market. This will not only result in improving the quality of their advice, but also help them in structuring better asset allocations customised to suit the investor.